2007
DOI: 10.1016/j.ccr.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

From nucleotides to ribozymes—A comparison of their metal ion binding properties

Abstract: It is undisputable that the fates of metal ions and nucleic acids are inescapably interwoven. Metal ions are essential for charge compensation of the negatively charged phosphate-sugar backbone, they are instrumental for proper folding, and last but not least they are crucial cofactors for ribozyme catalysis. Considerable progress has been achieved in the past few years on the identification of metal ion binding sites in large DNA and RNA molecules, like in ribozymes including the ribosome. Hereby, most inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
179
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 161 publications
(167 reference statements)
10
179
1
Order By: Relevance
“…However it has been shown that around 10 % of the total negative charge is compensated by metal ions that are site specifically bound (5). In order to be active, RNA molecules need to adopt complex three dimensional structures, stabilized by a large number and variety of tertiary contacts.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However it has been shown that around 10 % of the total negative charge is compensated by metal ions that are site specifically bound (5). In order to be active, RNA molecules need to adopt complex three dimensional structures, stabilized by a large number and variety of tertiary contacts.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be active, RNA molecules need to adopt complex three dimensional structures, stabilized by a large number and variety of tertiary contacts. In this folding process, localized pockets of accumulated negative charge are formed, that strongly bind positively charged ions, that is Na + , K + , Ca 2+ and Mg 2+ , the most abundant solvated metal ions in cells (5). In particular, Mg 2+ has been shown to perform both a structural and a catalytical role.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations